The stability of the thermohaline circulation in global warming experiments - Schmittner, Andreas; Stocker, Thomas F. (American Meteorological Society, 1999)
A simplified climate model of the coupled ocean–atmosphere system is used to perform extensive sensitivity studies concerning possible future climate change induced by anthropogenic greenhouse gas emissions. Supplemented with an active atmospheric hydrological cycle, experiments with different rates of CO2 increase and different climate sensitivities are performed. The model exhibits a threshold value of atmospheric CO2 concentration beyond which the North Atlantic Deep Water formation stops and never recovers. For a climate sensitivity that leads to an equilibrium warming of 3.6°C for a doubling of CO2 and a rate of CO2 increase of 1% yr−1, the threshold lies between 650 and 700 ppmv. Moreover, it is shown that the stability of the thermohaline circulation depends on the rate of increase of greenhouse gases. For a slower increase of atmospheric pCO2 the final amount that can be reached without a shutdown of the circulation is considerably higher. This rate-sensitive response is due to the uptake of heat and excess freshwater from the uppermost layers to the deep ocean. The increased equator-to-pole freshwater transport in a warmer atmosphere is mainly responsible for the cessation of deep water formation in the North Atlantic. Another consequence of the enhanced latent heat transport is a stronger warming at high latitudes. A model version with fixed water vapor transport exhibits uniform warming at all latitudes. The inclusion of a simple parameterization of the ice-albedo feedback increases the model sensitivity and further decreases the pole-to-equator temperature difference in a greenhouse climate. The possible range of CO2 threshold concentrations and its dependency on the rate of CO2 increase, on the climate sensitivity, and on other model parameters are discussed.